Analysis Of Light Color Type And Duration Of Exposure To Light On The Growth And Production Of Shallots (Allium Cepa L.) - Cakra Baso Ma’dika; Taruna Shafa Arzam AR; Akmal Akmal (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose: The purpose of this research is to determine the effect of the color of LED light on the growth of shallot plants (Allium cepa L.). with the duration of illumination indoors. Methodology: The research used a randomized group design. There are seven treatments consisting of one treatment using sunlight (P0), and six treatments of artificial light each using 20-watt LED lamps. The six treatments of artificial light were conducted indoors using different light colors and durations of illumination. The six treatments are: red light color and a duration of 12 hours (P1), red light color and a duration of 15 hours (P2), blue light color and a duration of 12 hours (P3), blue light color and a duration of 15 hours (P4), white light color and a duration of 12 hours (P5), white light color and a duration of 15 hours (P6). Each treatment consists of 4 plants, totaling 28 plant samples. The production data of the plants was analyzed using variance analysis. Results: The observations indicated that the effects of light color and duration of exposure on the growth and production of red onion plants did not show significant differences, but were better compared to the sunlight exposure treatment based on all observed parameters, which included the number of leaves, plant height, bulb diameter, bulb weight, number of bulbs, and harvest age of the red onion plants. Novelty: This research is expected to provide useful guidance for farmers and business actors in practicing more efficient and sustainable shallot cultivation. Conclusion: Based on the research conducted, red onion plants are very suitable for areas with cooler temperatures; it is recommended to use a fan to regulate the room's heat, because red onion plants can grow and develop in areas with cooler temperatures. Type of Paper: This writing is a Research Article.